Single-cell sequencing of tumor-associated macrophages in a Drosophila model - Khalili, Dilan; Mohammed, Mubasher; Kunc, Martin; Sindlerova, Martina; Ankarklev, Johan; Theopold, Ulrich (Frontiers in Immunology, 2023)
Introduction Tumor-associated macrophages may act to either limit or promote tumor growth, yet the molecular basis for either path is poorly characterized. Methods We use a larval Drosophila model that expresses a dominant-active version of the Ras-oncogene (RasV12) to study dysplastic growth during early tumor progression. We performed single-cell RNA-sequencing of macrophage-like hemocytes to characterize these cells in tumor- compared to wild-type larvae. Hemocytes included manually extracted tumor-associated- and circulating cells. Results and discussion We identified five distinct hemocyte clusters. In addition to RasV12 larvae, we included a tumor model where the activation of effector caspases was inhibited, mimicking an apoptosis-resistant setting. Circulating hemocytes from both tumor models differ qualitatively from control wild-type cells—they display an enrichment for genes involved in cell division, which was confirmed using proliferation assays. Split analysis of the tumor models further reveals that proliferation is strongest in the caspase-deficient setting. Similarly, depending on the tumor model, hemocytes that attach to tumors activate different sets of immune effectors—antimicrobial peptides dominate the response against the tumor alone, while caspase inhibition induces a shift toward members of proteolytic cascades. Finally, we provide evidence for transcript transfer between hemocytes and possibly other tissues. Taken together, our data support the usefulness of Drosophila to study the response against tumors at the organismic level.